A neutral paddlewheel-type diruthenium(III) complex with benzamidinato ligands: Synthesis, crystal structure, magnetism, and electrochemical and absorption properties. (4th November 2017) - Kataoka, Yusuke; Mikami, Saki; Sakiyama, Hiroshi; Mitsumi, Minoru; Kawamoto, Tatsuya; Handa, Makoto
Graphical abstract: A neutral paddlewheel-type diruthenium(III) complex coordinated with benzamidinato (bam) ligands [Ru2 (bam)4 Cl2 ]·H2 O (1 ) was synthesized and characterized. The magnetic study and DFT calculations proved that1 has a triplet state ( S = 1) and a unique electronic structure π 4 δ 2 π *2 σ 2 . Abstract: A new neutral diruthenium(III) complex coordinated with benzamidinato (bam) ligands, [Ru2 (bam)4 Cl2 ]·H2 O (1 ), was synthesized and characterized, and its electronic structure was closely investigated via magnetic susceptibility, absorption spectrum, cyclic voltammetry, and density functional theory (DFT) calculations. Single crystal X-ray diffraction analysis revealed that complex1 has a typical paddlewheel-type structure with a RuRu bond (bond length: 2.342(1) Å), in which the diruthenium (Ru2 ) core is coordinated by four equatorially μ-bridging bam ligands and two axial Cl − ions. The magnetic study and DFT calculations proved that complex1 has a triplet spin state ( S = 1) and a unique electronic structure (π 4 δ 2 π *2 σ 2 ). Absorption spectral feature and electrochemical property of complex1 were also carefully investigated both experimentally and theoretically in this study.